Recomendações de atividade física, comportamento sedentário e duração de sono em pré-escolares: associações com as habilidades motoras fundamentais - Mota, Jessica Gomes (2020)
Introduction: the behaviors of the integrated movement that make up the 24 hours of the day are evidenced in the recommendations of the World Health Organization (WHO), according to which children should have adequate time in physical activities, little exposure to screen-based entertainment and good hours of sleep. Such behaviors coexist and simultaneously impact the health and well-being of preschoolers. Adherence to physical activity, sedentary behavior and sleep can be related to the acquisition of fundamental motor skills (FMS), considering the development of HMF as a dynamic and reciprocal process, through involvement in physical activity in early childhood. Objective: to analyze the possible associations between integrated behavior (physical activity, sedentary behavior and sleep duration) of movement and HMFs in preschoolers. Methodology: this is a quantitative research with a descriptive, correlational and cross-sectional character. The sample consisted of children of both genres (78 boys) aged between three and five years (4.47 ± 0.78), from six Reference Centers in Early Childhood Education (CREIs) in the city of João Pessoa-PB (Brazil). Physical activity was evaluated using accelerometry (Actigraph, model WGT3-X, Florida) and the HMF was through the Test of Gross Motor Development-2 (TGMD-2, ULRICH, 2000). Sedentary behavior and sleep duration were measured through interviews with the children's parents/guardians. Descriptive analyzes and the association between movement behaviors and HMFs were carried out through compositional analysis in the R software (R Core Team, version 3.6.1, 2019). RESULTS: the children had an average of 230 min/day of total physical activity, 14 min/day of MVPA and low HMF scores for age and sex. Boys have higher scores on object control skills when compared to girls (p = 0.03). No child adhered to the three movement behaviors simultaneously within the 24-hour period. The time spent on AFMV behavior was the one with the least codependency within the composition of the day. When considered as a composition, the 24 hours of movement significantly predicted the locomotion score (P <0.0001; r2 = 0.31), object control (P <0.0001; r2 = 0.19) and the total HMF score (P <0.0001; r2 = 0.35), even after adjusting for sex, age and BMI. CONCLUSION: It was observed that when adjusted for age, BMI and sex, the 24-hour behaviors, in compositional analysis, significantly predicted HMF. There were no significant differences between adherence/non-adherence to different movement behaviors and gender. Boys had higher scores on object control skills when compared to girls.